PUBLIC RECEPTION AS A FORMCONSIDERATIONS AND RESOLUTIONS OF THE APPEAL OF CITIZENS (Journal of actual problems of jurisprudence, 2019)
In this article the author writes about the public reception yavlyutsya which one of the forms review and permit citizens'